Comparative oral drug classification systems: Acetazolamide, azithromycin, clopidogrel, and efavirenz case studies - Mora, Maria Julia (2018)
Biopharmaceutics classification systems based on the properties of solubility and permeability or the extension of metabolism are very important tools in the early stages of the development and regulatory stages of new products. However, until now, there was no clear understanding between the interplay among these classification systems. Therefore, the main objective of this work was to make a comparison of concepts of BCS and BDDCS to understand what are the key factors that allow for the integration of these biopharmaceutics classification systems. Also, the suitability of an in situ single-pass intestinal perfusion assay in rats (SPIP) development was assessed by us to determine the limit between high and low permeability following what the FDA BCS guidance suggests. An excellent correlation was found between the values of permeability obtained by applying SPIP assays and the extensions of the metabolism of the set of compounds studied in this work, with the exception of three compounds that showed disparity between their permeability coefficients (P eff ), obtained herein by SPIP, and their metabolism (acetazolamide, azithromycin, and efavirenz). Discrepancies allowed us to elucidate the interrelationship between BCS and BDDCS.